A Critique on the Book Life, Time and Historiography of Wassaf - Sayyid Abolfazl Razavi; Hossein Hozhabrian (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The era of Ilkhanid's rule, according to historical requirements, was accompanied by the growth of Persian historiography. Numerous historiographical works that appeared in the Ilkhanids realm and on the other hand in the realm of the Mamluks have strengthened the record of Islamic-Iranian historiography and eased the way for understanding the history of this era. Among them, Wassaf, a literate-historian who has used a different method in presenting historical interpretations in literary style and historical structure played a special role. The book Life, Time and Historiography of Wassaf is important because it deals with such a historian and has been studied for this reason. The critique of this book is done by the distinction between the two concepts; explanation and interpretation, as well as differing concepts of historian and history-researcher, further the attention to both negative and positive approaches, pursues this goal to show that there is a difference between understanding of history and historiography and current interpretive understanding of the historian’s explanation, should not be considered historiography.